Formation of CoS2 Nanobubble Hollow Prisms for Highly Reversible Lithium Storage - Yu, Le (2017)
Metal–organic frameworks (MOFs) have been intensively used as the templates/precursors to synthesize complex hollow structures for various energy-related applications. Herein we report a facile two-step diffusion-controlled strategy to generate novel MOFs derived hierarchical hollow prisms composed of Nanosized CoS2 bubble-like subunits. Uniform zeolitic imidazolate framework-67 (ZIF-67) hollow prisms assembled by interconnected nanopolyhedra are first synthesized via a transformation process. Afterwards, these ZIF-67 building blocks are converted into CoS2 bubble-like hollow particles to form the complex hollow prisms through a sulfidation reaction with an additional annealing treatment. When evaluated as an electrode material for lithium-ion batteries, the as-obtained CoS2 nanobubble hollow prisms show remarkable electrochemical performance with good rate capability and long cycle life.